Gene expression and dispersion profiles associated with water consumption and general activity in grazing beef cattle - Watanabe, Rafael Nakamura [UNESP]; Bernardes, Priscila Arrigucci; Berça, Andressa Scholz [UNESP]; Fonseca, Natalia Vilas Boas [UNESP]; Cunha, Samla Marques Freire [UNESP]; Rodrigues, Julia Lisboa [UNESP]; Buzanskas, Marcos Eli [UNESP]; Cardoso, Tainã Figueiredo; Faro, Lenira El; Reis, Ricardo Andrade [UNESP]; Coutinho, Luiz Lehmann; Regitano, Luciana Correia de Almeida; et al. (Springer Nature, 2025)
Selecting animals to reduce their environmental impact is important for implementing sustainable livestock production systems. Identifying genes influencing water consumption and general activity in grazing beef cattle can aid in selecting efficient animals. This work aimed to verify the differential gene expression (DE) and dispersion (DD) profiles associated with water consumption frequency (WCF) and general activity (GA) in grazing Nelore and F1 (Nelore × Angus) cattle. Behavioral data were collected from 36 to 33 Nelore and F1 animals, respectively, for 12 h daily over four days. For the RNA sequencing, ten animals (five with higher frequency and five with lower frequency) were selected for WCF and GA in each breed. The functional and enrichment analyses revealed that the genes found in the WCF animals were associated with glucose metabolism (LOC520336 and GCNT2), kidney physiology (ATP6V0A4), the immune system (CD96 and KLRD1), adaptive capacity, fat deposition (THBS1), and blood pressure maintenance (CDCA7). The genes influencing GA were associated with adaptation to environmental temperature and challenging conditions (SLC16A6, STOM, CLTA and IFNAR2). More pronounced changes and functional enrichments was observed in Nelore cattle, particularly for WCF. F1 cattle showed more differential dispersion genes related to general activity, suggesting variability in gene expression might be more relevant for this trait in the crossbred animals. In conclusion, the genes identified in this study were associated with several important traits related to the adaptive capacity of animals. These genes can elucidate and help select animals that are more adapted to challenging environments and reduce their environmental impact, leading to a more sustainable livestock production system.